Isolation and characterization of antimicrobial compounds from Cotinus coggygria Scop. ethyl acetate extract - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2020)
Background and Aims: Cotinus coggygria leaves are traditionally used in the treatment of various diseases, including their use for antifungal purposes. The aim of this study was to evaluate the antimicrobial activity of the extracts of C. coggygria and to discover compounds that may be responsible for the activity of the most active extract. Methods: The antimicrobial activities of extracts and compounds were assessed by the microbroth dilution technique. Major compounds of active extract were isolated using chromatographic methods and identified by spectroscopic methods. Results: Diethylether (CCD), ethyl acetate (CCEA), methanol (CCM), ethanol (CCE) and water (CCW) extracts of C. coggygria exhibited noticeable antifungal activities against Candida albicans with MIC values of 39, 4.9, 4.9, 4.9 and 9.8 mu g/mL, respectively. Also, CCEA extract showed good antibacterial activity against Proteus mirabilis with an MIC value of 156 mu g/mL. Two major compounds, gallic acid and methyl gallate, were isolated from CCEA, the most active extract. Gallic acid was found to be highly active against C. albicans and C. tropical is with an MIC value of 9.8 mu g/mL (for both fungi). In addition, gallic acid showed moderate antimicrobial activity against Staphylococcus aureus, S. epidermidis and C. parapsilosis with MIC values of 78, 156 and 156 mu g/mL, respectively. Conclusion: This study is the first study to reveal the compounds responsible for the activity of CCEA extract with antifungal activity. These results suggest that gallic acid, along with other phenolic compounds, is responsible for the antifungal activity of CCEA. Also, it confirms the ethnobotanical use of C. coggygria for antifungal purposes.
Keywords: Antimicrobial activity; Candida species; Cotinus coggygria; ethyl acetate extract; gallic acid; methyl gallate; ANTIFUNGAL ACTIVITY; ETHANOL EXTRACT; IN-VITRO; ANTIBACTERIAL; ANTIOXIDANT; LEAVES; ENGL.